Who remits and why? Evidence on internal migrant remittances from Vietnam and Thailand - Rasadhika Sharma; Ulrike Grote (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2018)
The paper analyses determinants and motivations of internal migrant remittances based on a unique data set that combines a household survey from three provinces in Vietnam and Thailand with a migrant tracing survey that was conducted in Ho Chi Minh City and the Greater Bangkok area. Using the Heckman model, we find that human capital, stronger family ties and better living conditions positively influence the migrant's decision to remit. In terms of the amount remitted, migrants engaged in the service sector remit lower shares of their income and remittances decrease as the household wealth increases. Furthermore, we explore the behavioral side of remittances by constructing proxy groups that represent each strand of migrant's motivation for remitting. We examine the relationship of these proxy groups and remittances to conclude that exchange or loan repayment motive underpinned by altruism is the strongest motivation in our case.
Keywords: F24; J61; O53; D90; 330; Remittances; Altruism; Self-interest; Heckman model; Thailand; Vietnam